Epidemiological profile of patients with nephropathy and the difficulties in access to treatment - Monteiro Sampaio, Rafaella Maria (2013)
Objective: To describe the epidemiological profile of patients undergoing treatment for renal replacement therapy in dialysis modality, and to identify the difficulties in its realization. Methods: This is a cross-sectional study conducted in Itapipoca-CE, comprising 35 patients with chronic renal failure (CRF). The general data was analyzed descriptively using absolute and percentage frequencies. Results: The epidemiological profile of patients shows a higher frequency of: males (19 - 54.3%) aged between 31 and 60 (24 - 68.6%), low education (29 - 82.8%), family incomes of 1 to 2 minimum wages (25 - 71.4%), living in houses of masonry (30 - 85.7%) with treated water provided in their homes (17 - 48.6%). The main signs and symptoms that led to seeking medical consultation were: general weakness (21 - 60.0%), nausea (19 - 54.3%), edema (18 - 51.4%) and lack of appetite (14 - 40.0%). The features most frequently mentioned by the patients as probable causes to CRF were: association of hypertension with diabetes mellitus (11 - 31.4%), hypertension (9 - 25.7%) and glomerulonephritis (5 - 14.3%). Most patients reported difficulty in obtaining medical appointment (25 - 71.4%) and scheduling/receiving exams (20 - 57.1%). Conclusion:The epidemiological profile of patients studied is marked by a low socioeconomic status. As aggravating factors to this situation, there was the difficulty in getting appointments, scheduling and performing diagnostic tests, which undermines the treatment.